Hepatic Mitochondrial SAB Deletion or Knockdown Alleviates Diet‐Induced Metabolic Syndrome, Steatohepatitis, and Hepatic Fibrosis. Issue 6 (10th October 2021) - Win, Sanda; Min, Robert W.M.; Zhang, Jun; Kanel, Gary; Wanken, Brad; Chen, Yibu; Li, Meng; Wang, Ying; Suzuki, Ayako; Aung, Filbert W.M.; Murray, Susan F.; Aghajan, Mariam; et al.
Abstract : Background and Aims: The hepatic mitogen‐activated protein kinase (MAPK) cascade leading to c‐Jun N‐terminal kinase (JNK) activation has been implicated in the pathogenesis of nonalcoholic fatty liver (NAFL)/NASH. In acute hepatotoxicity, we previously identified a pivotal role for mitochondrial SH3BP5 (SAB; SH3 homology associated BTK binding protein) as a target of JNK, which sustains its activation through promotion of reactive oxygen species production. Therefore, we assessed the role of hepatic SAB in experimental NASH and metabolic syndrome. Approach and Results: In mice fed high‐fat, high‐calorie, high‐fructose (HFHC) diet, SAB expression progressively increased through a sustained JNK/activating transcription factor 2 (ATF2) activation loop. Inducible deletion of hepatic SAB markedly decreased sustained JNK activation and improved systemic energy expenditure at 8 weeks followed by decreased body fat at 16 weeks of HFHC diet. After 30 weeks, mice treated with control–antisense oligonucleotide ( control‐ASO ) developed steatohepatitis and fibrosis, which was prevented by Sab‐ASO treatment. Phosphorylated JNK (p‐JNK) and phosphorylated ATF2 (p‐ATF2) were markedly attenuated by Sab‐ASO treatment. After 52 weeks of HFHC feeding, control N‐acetylgalactosamine antisense oligonucleotide (GalNAc‐ Ctl‐ASO ) treated mice fed the HFHC diet exhibited progression of steatohepatitis and fibrosis, but GalNAc‐ Sab‐ASO treatment from weeks 40 to 52 reversed these findings while decreasing hepatic SAB, p‐ATF2, and p‐JNK to chow‐fed levels. Conclusions: Hepatic SAB expression increases in HFHC diet–fed mice. Deletion or knockdown of SAB inhibited sustained JNK activation and steatohepatitis, fibrosis, and systemic metabolic effects, suggesting that induction of hepatocyte Sab is an important driver of the interplay between the liver and the systemic metabolic consequences of overfeeding. In established NASH, hepatocyte‐targeted GalNAc‐ Sab‐ASO treatment reversed steatohepatitis and fibrosis.